Eccentric Exercise Guidelines for Managing Rheumatoid Arthritis: Findings From a Randomized Controlled Trial - Amidu Yekini; Jeanne Martin Grace (Health Science Reports)
ABSTRACT Background and Aims There are strong indications that the prevalence of poor body composition in RA patients is reportedly high. Evidence in the literature suggests that RA patients have low functional ability, which may negatively impact their work productivity and physical activity levels. Given the beneficial effects of an eccentric exercise intervention on RA conditions, there is still no sufficient information about the eccentric exercise guidelines for managing RA. This study aimed to develop eccentric exercise guidelines for managing RA conditions. Methods Eccentric exercise guidelines for managing RA were developed in three phases: A scoping literature review, an experimental pretest‐posttest randomized control trial, and synthetization of the outcomes. Thirty‐seven RA patients participated in the experimental pretest‐posttest study and were randomized into control and exercise groups. Results Eccentric exercise interventions show positive effects on body composition, blood pressure, work‐related performance, and physical activity levels in RA patients. Proposed management guidelines for RA conditions include 40‐min eccentric exercises three times weekly. It is proposed that an eccentric exercise intervention should be progressive to elicit maximum benefits for RA patients. Conclusion An eccentric‐concentrated exercise intervention is safe and provides a specific exercise trajectory for managing RA conditions. Evidence‐based eccentric guidelines were developed to improve RA patients' body composition, physical activity levels, and cardiovascular risk factors. The guidelines could also benefit physical functioning and work productivity in RA patients. It should be used alongside the existing guidelines for managing RA disease conditions.